No Effect of Anodal Transcranial Direct Current Stimulation (tDCS) Over hMT+ on Motion Perception Learning - Larcombe, Stephanie J.; Kennard, Christopher; O’Shea, Jacinta; Bridge, Holly (Frontiers in Neuroscience, 2019)
Background: Human visual cortical area hMT+, like its homolog MT in the macaque monkey, has been shown to be particularly selective to visual motion. After damage to the primary visual cortex (V1), patients often exhibit preserved ability to detect moving stimuli, which is associated with neural activity in area hMT+. As an anatomical substrate that underlies residual function in the absence of V1, promoting functional plasticity within hMT+ could potentially boost visual performance despite primary visual cortical damage. Objective: To establish in healthy participants whether it is possible to use transcranial direct current stimulation (tDCS) over hMT+ to potentiate learning of visual motion direction discrimination. Methods: Twenty-one participants were trained daily for 5 days on a visual motion direction discrimination task. Task difficulty was increased as performance improved, by decreasing the proportion of coherently moving dots, such that participants were always performing at psychophysical threshold. tDCS, either anodal or sham, was applied daily during 20 min of training. Task performance was assessed at baseline and at the end of the training period. Performance was also compared with a third group of 10 participants from an earlier study who had undergone the same procedures but without tDCS. Results: All participants showed improved task performance both during and after training. Contrary to our hypothesis, anodal tDCS did not further improve performance compared to sham stimulation or no stimulation. Bayesian statistics indicated weak evidence in favor of the null hypothesis. Conclusion: This study found no evidence for a robust effect of anodal tDCS over hMT+ on visual motion direction discrimination learning in the young healthy visual system, although more subtle effects may have been missed in the relatively small sample size.